STUDYING OF A MASSAGE SERVICE MODEL FOR THE ELDERLY IN COMMUNITY HEALTH SERVICE CENTER 8 BOONRAWD RUNGROONG, BANA DISTRICT, BANGKOK - Piriyabenjawat , Jutarat (Dusit Thani College Journal, 2021)
This research aimed to study the behavior of health massage service in the health care of the elderly. In the community, health service centers 8 Boonrawd Rung, Bangna District, Bangkok, and to present a form of health massage service in the elderly health care for spa business, this research was utilized the mix method to collect the data, in terms of qualitative approach an informal interview with a focus interview. Using a semi-structured interview (Semi-structure Interview) by focusing on the study of 40 elderly in the community of Public Health Center 8 Boonrawd Roong, Bang Na, Bangkok. While the quantitative approach was employed the Descriptive Statistics, i.e. frequency and percentage used for analyzing the basic data of the sample. And information about health decision-making behavior and The Reference Statistics, such as Chi-square, were used to analyze the relationship between the baseline data of the sample and data on the behavior of health massage services in the health care of the elderly in the community, Public Health Center 8 Boonrod Rung Ruang, Bangna District, Bangkok. The research found that 37 of the respondents between 76-80 years old. They almost female and they all get married. They are housewife/househusband and having Monthly income less than 5,000 baht, their education level is lower than primary school. Almost of them might choose Full-body massage by reasons of the most relaxation we got. The people who were most important to choosing a massage parlor found that most of the respondents had friends, who were the number one most important to choosing a massage parlor. When choosing a massage service, most respondents were unable to specify a massage service period. Depending on convenience. People who went to a massage, found that the majority of people used a massage alone. The frequency of using the massage service was found that most of them used less than 1 massage / month and most were satisfied with the price of 100-200 baht massage per time, and most of them experienced pain and pain which is important to choose. Most massages and most of them agree that massage is the number one effect on relaxation/ comfort.